Active tectonic evolution of two adjoining thrust sheets in the Indo-Myanmar fold-thrust belt, Northeast India - Kshetrimayum, Alexander S.; Goswami, Pradeep K.; Chang, Chung-Pai; Chang, Wu-Lung; Joshi, Lalit Mohan (Frontiers in Earth Science, 2024)
The active tectonic aspects of the Indo-Myanmar Range (IMR) have not yet been studied in detail in spite of the fact that it's seismically active. In the present study qualitative and quantitative geomorphic analyses have been carried out to understand the active tectonic evolution of Nungba, and Barak-Makru thrust sheets (NBTS and BMTS) in the central part of IMR. The focus of the study is on understanding the active spatial growth pattern of adjacent thrust sheets in an evolving mountain range and providing baseline data for further detailed seismotectonic and seismic hazard vulnerability analyses. Drainage characteristics, disposition of landforms and statistical analyses of Normalized Steepness Index (ksn), Hypsometric Integral (HI) and Transverse Topography Symmetry Factor (T), computed for a total of 164 4 th -order drainage basins, reveal that both of these adjoining thrust sheets are actively uplifting. Higher values of ksn (mode = 111) and HI (mode = 0.46) in NBTS suggest its faster uplift than the BMTS, which has comparatively lower values of ksn (mode = 56) and HI (mode = 0.43).Moreover, the northern parts of the both the thrust sheets are uplifting faster than their southern parts due to along-strike variations in the movement on their basal thrusts, as a result of which the NBTS has been south-southeastwardly down-tilting and the BMTS is south-southwestwardly down-tilting. The study reveals that both the adjacently lying NBTS and BMTS have almost the same spatial growth patterns that are mainly controlled by the movements on their basal thrusts.